The burden of acute malnutrition among children under five in conflict-afflicted Gaza strip: prevalence and associated factors - Albelbeisi, Ahmed; Zinszer, Kate; El Bilbeisi, Abdel Hamid; Abuzerr, Samer (Frontiers in Nutrition, 2024)
Background: This study aims to assess the prevalence and associated factors of Severe Acute Malnutrition (SAM) and Moderate Acute Malnutrition (MAM) among children in this region during a period of conflict. Methods: A cross-sectional study was conducted with a sample of 1,200 children under five years old, selected through stratified random sampling from three governorates in the Gaza Strip. Data were collected using structured interviews and physical examinations, including Mid-Upper Arm Circumference (MUAC) measurements to determine nutritional status based on established cut-off points. Statistical analyses were performed using IBM-SPSS, version 26. Results: Among the 1,200 children screened, 605 (50.8%) were males and 595 (49.2%) were females. The age distribution of the children screened showed that 48.4% (n=581) fall within the range of 6 months to <24 months category and 51.6% (n=619) fall within the range of 24-60 months. Overall, 58.3% of children live in schools, 26.6% live in houses, and 15.2% reside in tents. The overall prevalence of malnutrition across all regions was 16.6%, including 6.7% with SAM and 9.7% with MAM. The prevalence of SAM is highest in North Gaza and South Gaza (both at 6.8%) and slightly lower in the Middle Zone (6.5%). For MAM, the highest prevalence is in South Gaza (11.5%), with Middle Zone showing the lowest rate (7.3%). Logistic regression analysis indicated that children living in houses had a higher likelihood of SAM (OR=2.36; 95% CI=1.39-3.99) and MAM (OR=1.44; 95% CI=1.13-1.84), and children living in schools had a higher likelihood of SAM (OR=2.79; 95% CI=1.35-5.74) and MAM (OR=2.08; 95% CI=1.14-3.80) compared to those in tents. Notably, children residing in North Gaza were significantly more likely to experience SAM (OR=13.2; 95% CI=6. 23-27.95) and MAM (OR=10.51; 95% CI=5.74-19.3) compared to those in South Gaza. Conclusion: The study highlights a high prevalence of malnutrition among children under five in the Gaza Strip, particularly among those living in houses, shelters and in the North Gaza governorate. These findings underscore the urgent need for targeted nutritional interventions and support for affected families in conflict zones.